An empirical clock to measure the dynamical age of star clusters. Issue Volume 14:Issue S351(2019) (May 2019) - Ferraro, Francesco R.
Abstract: The observational properties of a special class of stars (the so-called Blue Straggler stars - BSSs) in Globular Clusters are discussed in the framework of using this stellar population as probe of the dynamical processes occurring in high-density stellar systems. In particular, the shape of the BSS radial distribution and their level of central segregation have been found to be powerful tracers of the level of the dynamical evolution of the hosting cluster, thus allowing the definition of an empirical chronometer able to measure the dynamical age of star clusters.